2007
DOI: 10.1016/j.jus.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasound-guided needle biopsy in the diagnosis of soft-tissue tumors

Abstract: KEYWORDSUltrasound-guided needle biopsy; Soft-tissue tumors; Musculoskeletal sonography.Abstract Soft-tissue tumors are not very common, but their diagnosis can be very difficult. In the final analysis, their diagnosis requires a biopsy, which must furnish a sufficient amount of material to allow a reliable histological diagnosis. The authors evaluated the diagnostic efficacy of ultrasound-guided needle biopsy in the diagnosis of soft-tissue tumors of the musculoskeletal system. The aim of the study was to opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…Our success rate was slightly higher than that reported by Battaglia et al. 20 In their study, sufficient material for histologic diagnosis was collected in 148 of 164 cases (90%). Our better performance was mainly due to the gauge of our needles (14G) being larger than that of their needles (15–18G).…”
Section: Discussioncontrasting
confidence: 63%
“…Our success rate was slightly higher than that reported by Battaglia et al. 20 In their study, sufficient material for histologic diagnosis was collected in 148 of 164 cases (90%). Our better performance was mainly due to the gauge of our needles (14G) being larger than that of their needles (15–18G).…”
Section: Discussioncontrasting
confidence: 63%
“…Bony PCBs are usually fluoroscopy-guided and performed with a trocar of 11 Gauge, with a percentage of diagnostic results ranging between 75% to 98% [14,17,18,22,27,[31][32][33]41]. Instead, PCBs for soft tissue lesions are generally ultrasound-guided and performed with a 14-gauge tru-cut needle, with a diagnostic result reported in literature ranging from 83% to 96% [12,13,19,20,29,32,33,[35][36][37][38][39][40][41][42][43][44]. The incidence of non-diagnostic PCB is higher in soft tissue than in bone lesions, probably due to the high presence of necrotic areas that could make histological interpretation more difficult [34,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, PCBs for soft tissue lesions are generally ultrasound-guided and performed with a 14-gauge tru-cut needle, with a diagnostic result reported in literature ranging from 83% to 96% [12,13,19,20,29,32,33,[35][36][37][38][39][40][41][42][43][44]. The incidence of non-diagnostic PCB is higher in soft tissue than in bone lesions, probably due to the high presence of necrotic areas that could make histological interpretation more difficult [34,43,44]. In our series, adequate material for diagnosis was obtained more frequently in bone (97%, 366/376), than in soft tissue (94%, 304/322).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 It can distinguish malignant versus benign musculoskeletal tumors 13 and guide their needle biopsy. 14 Use of intraoperative US (IOUS) in cancers such as breast cancer, 15 liver cancer, 16 and tongue cancer 17 has been well established. 18 Krekel et al 15 reported that IOUS-guided breast cancer excision achieved a significantly clearer margin than did palpation-guided surgery, which reduced the need for re-excision, mastectomy, radiotherapy, and unnecessary resection of healthy breast tissue.…”
Section: Introductionmentioning
confidence: 99%